2006
DOI: 10.1002/bjs.5270
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic risk factor clustering and insulin resistance in healthy male relatives of men with intermittent claudication

Abstract: Raised levels of PAI-1, tPA, D-dimer and estimated insulin resistance were present in the healthy male first-degree relatives of men with intermittent claudication. These data support the hypothesis of fibrinolytic risk factor clustering in this high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…In the univariate analyses we found that insulin resistance was negatively associated with sICAM‐1 and positively associated with IL‐6 and D‐dimer levels. The IL‐6 and D‐dimer findings, which were not sustained in the multivariate analyses, are consistent with observations in older adults (16) and indicate increased inflammation and coagulation with increasing insulin resistance. In a prior study of lean and obese middle‐aged adults sICAM‐1 was independently negatively associated with insulin sensitivity, indicating higher sICAM‐1 levels with increasing insulin resistance (17).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the univariate analyses we found that insulin resistance was negatively associated with sICAM‐1 and positively associated with IL‐6 and D‐dimer levels. The IL‐6 and D‐dimer findings, which were not sustained in the multivariate analyses, are consistent with observations in older adults (16) and indicate increased inflammation and coagulation with increasing insulin resistance. In a prior study of lean and obese middle‐aged adults sICAM‐1 was independently negatively associated with insulin sensitivity, indicating higher sICAM‐1 levels with increasing insulin resistance (17).…”
Section: Discussionsupporting
confidence: 85%
“…In middle‐aged women, CRP is independently associated with fasting insulin levels (15). In older adults elevated D‐dimer levels accompany insulin resistance (16). In middle‐aged adults sICAM‐1 has been shown to be associated with insulin resistance (17), although other studies show no such association (18).…”
Section: Introductionmentioning
confidence: 99%
“…The study population comprised 318 clinically healthy white males of European origin, characterised for the presence of the MetS and in whom stored plasma was available for analysis of NEP. Participant recruitment has been published previously (17;18). In brief, all subjects were free from clinical cardiovascular disease or previously diagnosed diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of fasting lipids, glucose, insulin and homeostasis model assessment (HOMA), tissue plasminogen activator (tPA) and plasminogen activator inhibitor-1 (PAI-1) were carried out as previously described. (17;18)NEP was assayed according to an original protocol (19) modified in our laboratory using the fluorogenic substrate succinoyl-Ala-Ala-Phe-7-amido-4-methylcoumarin (200 μM) in a coupled assay with leucine aminopeptidase (50 μg/ml) in 50 mM Hepes/NaOH, 200 mM NaCl, 10 μM ZnCl 2 , 1% DMSO, pH 6.8 at room temperature in the dark. Fluorescence was measured using a Biotek Synergy HT plate reader (λ excitation = 380 nm and λ emission = 460 nm).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that IR was associated with atherosclerosis 14,15 and elevation of fibrinogen levels 16,17 as well as plasminogen activator inhibitor type 1 activity level. 16,[18][19][20] Other previous studies reported that an elevated fibrinogen level, 21,22 plasminogen activator inhibitor type 1 activity level, 23,24 and atherosclerosis [25][26][27] are associated with cerebral infarction. Therefore, we conclude that IR is associated with cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%